A positive electrode material, a positive electrode sheet including the positive electrode material, and a sodium-ion battery
Patent Information
- Application Number
- CN202211117894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-09-14
AI Technical Summary
Existing cathode materials for sodium-ion batteries suffer from poor structural and cycle stability, especially transition metal oxide materials.
By using sodium transition metal oxide cathode materials containing Co, K, and optional M elements, and by controlling the doping amount and ratio of K element, combined with P2 phase stacking structure and appropriate particle size and compaction density, cathode materials with high structural stability and cycle stability are prepared.
It improves the specific capacity, cycle performance, and energy density of sodium-ion batteries, and has excellent rate performance and interface stability.
Smart Images

Figure CN117747809B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a positive electrode material, a positive electrode sheet including the positive electrode material, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries have broad application prospects due to their comprehensive advantages such as good safety, low cost, abundant resources and environmental friendliness. Their working principle is similar to that of lithium-ion batteries, mainly using sodium ions to store and release energy by intercalating and deintercalating between the positive and negative electrodes.
[0003] Currently, the cathode materials for sodium-ion batteries mainly fall into three categories: transition metal oxides, polyanionic compounds, and Prussian blue systems. Among them, transition metal oxides have attracted widespread attention and research due to their highest theoretical specific capacity. However, these materials suffer from problems such as poor structural stability and poor cycle stability. Summary of the Invention
[0004] To overcome the shortcomings of existing technologies, the present invention provides a cathode material, a cathode sheet including the cathode material, and a sodium-ion battery. The cathode material has good structural stability and cycle stability, and can overcome the problems of poor cycle performance and poor rate performance of existing cathode materials for sodium-ion batteries.
[0005] The objective of this invention is achieved through the following technical solution:
[0006] A cathode material, wherein the cathode material is a sodium transition metal oxide comprising Co, K, and optionally M, wherein the M element is selected from at least one of Al, Mg, Ti, Mn, Te, Ni, W, Nb, Zr, La, or Y; and the molar amount of K element per mole of cathode material is n. K The molar amount of Co in a unit mole of cathode material is n. Co The molar amount of element M in one mole of cathode material is n. M The n K and n Co+ n M The ratio is 0 <n K / n Co+ n M <0.005.
[0007] In some embodiments, doping with K can improve the specific capacity of the cathode material. By further controlling the amount of K doping, the specific capacity of the cathode material can be fully utilized.
[0008] In some embodiments, the term can be optional or not.
[0009] In some embodiments, said n K and n Co+ n M has a ratio of 0.001, 0.002, 0.003 or 0.004.
[0010] In some embodiments, the molar amount n of element K per mole of positive electrode material K is 0<n K <0.005, preferably 0.0025<n K <0.0035, for example n A is 0.0010, 0.0015, 0.0020, 0.0025, 0.0030, 0.0035, 0.0040 or 0.0045.
[0011] In some embodiments, the molar amount n of element M per mole of positive electrode material M is 0≤n M <0.05, for example 0.01, 0.02, 0.03, 0.04 or 0.045.
[0012] In some embodiments, the positive electrode material further comprises element Na, and the molar amount n of element Na per mole of positive electrode material Na is 0.60<n Na <0.84, preferably 0.70<n Na <0.76, for example n Na is 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.80, 0.82 or 0.84.
[0013] In some embodiments, the chemical formula of the positive electrode material is: Na x K a Co 1-b M b O2, 0.6<x<0.84, 0<a<0.005, 0≤b<0.05, wherein M is as defined above.
[0014] In some embodiments, the positive electrode material has a P2 phase stacking structure and belongs to the P63mc space group.
[0015] In some embodiments, the median particle size of the positive electrode material is 5 μm to 20 μm, preferably 5 μm to 17 μm, for example 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm. The positive electrode material with the median particle size can effectively improve the electrochemical kinetic performance and rate performance during charge and discharge, so that the battery has high specific capacity and cycle performance.
[0016] In some embodiments, the compaction density of the positive electrode material is 3.0–4.5 g / cm³. 3 More preferably, it is 3.5–4.2 g / cm³. 3 This can effectively increase the compaction density of the electrode, thereby increasing the energy density of sodium-ion batteries.
[0017] In some embodiments, X-ray diffraction testing shows that the cathode material has at least a (002) peak, a (102) peak, a (103) peak, and a (104) peak, wherein the (002) peak has the highest intensity, and the peak intensities of the (102) peak, (103) peak, and (104) peak satisfy I (103) (104) (102) At this point, the rate performance and cycle stability of the cathode material are better.
[0018] This invention also provides a method for preparing the above-mentioned cathode material, the method comprising the following steps:
[0019] (1) A coprecipitate is prepared by coprecipitation of a soluble Co salt and a soluble salt optionally containing element M, and the coprecipitate is sintered to obtain Co salt doped with element M. 1-b M b )3O4, where 0≤b<0.05;
[0020] (2) According to the stoichiometric ratio, (Co) 1-b M b The cathode material is prepared by sintering a mixture of 3O4, Na source, and K-containing compound in an air atmosphere.
[0021] Specifically, the specific steps of the co-precipitation reaction in step (1) include:
[0022] Soluble Co salts and optionally soluble salts containing element M are mixed in a molar ratio of Co to M of (1-b):b, and added to a solvent to obtain a mixed solution. A precipitant and a complexing agent are added to the mixed solution to obtain a reaction solution. The pH of the reaction solution is adjusted to 6-8, and the reaction solution is subjected to a coprecipitation reaction at a predetermined temperature and stirring rate to obtain a coprecipitate.
[0023] Further, in step (1), the soluble Co salt is one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate; the soluble salt containing element M is one or more of nitrate, sulfate, chloride, and acetate containing element M; and the compound containing element K is at least one of KOH, K2CO3, KCl, and KHCO3.
[0024] Further, in step (1), the solvent for the coprecipitation reaction is one or more of deionized water, methanol and ethanol.
[0025] Further, in step (1), the precipitant for the coprecipitation reaction is one or more of NaOH, KOH, Na2CO3, K2CO3, NaHCO3 and KHCO3. It should be noted that before adding the precipitant to the mixed solution, the precipitant may be pre-prepared to obtain a precipitant solution, and the solvent used for preparing the precipitant solution may be one or more of deionized water, methanol and ethanol.
[0026] Further, the molar concentration in the precipitant solution is 0.1 to 3 mol / L, more preferably 1 to 3 mol / L.
[0027] Further, in step (1), the complexing agent for the coprecipitation reaction is one or more of ammonia water, ammonium carbonate and ammonium bicarbonate. It should be noted that before adding the complexing agent to the mixed solution, the complexing agent may be prepared to obtain a complexing agent solution, and the solvent used for preparing the complexing agent solution may be one or more of deionized water, methanol and ethanol.
[0028] Further, in step (1), the temperature of the coprecipitation reaction is 25 to 85°C; the time of the coprecipitation reaction is 24 to 36 h.
[0029] Further, in step (2), the Na source is at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0030] Further, in step (2), (Co 1-b M b )3O4, the Na source and the compound containing K element are in a molar ratio of Na, Co, K of (0.6 to 0.84):(1-b):a, where 0<a<0.005, 0≤b<0.05, preferably, the molar ratio of Na to Co is (0.70 to 0.78):1.
[0031] Further, in step (2), the sintering temperature is 750 to 950°C, more preferably 800 to 900°C; the sintering time is 20 to 40 h, more preferably 24 to 36 h.
[0032] In the preparation process of the positive electrode material of the present invention, through comprehensive regulation of the types of reactants, the parameters of the coprecipitation reaction, the types of product elements and the doping amount, the positive electrode material can have the specific chemical composition and structure described in the present invention, which can greatly improve the electrochemical performance of the positive electrode material, as well as increase the specific capacity, cycle performance, rate performance and energy density of the sodium-ion battery.
[0033] The present invention also provides a positive electrode sheet, wherein the positive electrode sheet comprises the above-mentioned positive electrode material.
[0034] Furthermore, the positive electrode sheet includes a current collector and a positive electrode material layer; the positive electrode material layer is disposed on at least one surface of the current collector; the positive electrode material layer includes the aforementioned positive electrode material.
[0035] Furthermore, the positive electrode material layer also includes a conductive agent and a binder.
[0036] Further, the conductive agent includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, or mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0037] Furthermore, the current collector includes, but is not limited to: aluminum foil, carbon-coated aluminum foil, perforated aluminum foil, stainless steel foil, polymer substrate coated with conductive metal, and any combination thereof.
[0038] Furthermore, the adhesive includes, but is not limited to: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), water-based acrylic resin, polyvinyl alcohol, polyvinyl butyral, polyurethane, fluorinated rubber, carboxymethyl cellulose (CMC), and polyacrylic acid (PAA).
[0039] Furthermore, the positive electrode sheet can be prepared according to conventional methods in the art. Typically, the positive electrode material and optional conductive agents and binders are dispersed in a solvent (e.g., NMP) to form a uniform positive electrode slurry. The positive electrode slurry is then coated onto a current collector, and after drying and other processes, the positive electrode sheet is obtained.
[0040] The present invention also provides a sodium-ion battery comprising the above-described positive electrode material, or comprising the above-described positive electrode sheet.
[0041] Beneficial effects:
[0042] (1) The cathode material provided by the present invention belongs to the P63mc space group, has a P2 phase stacking structure, has high crystal structure stability, and has excellent cycle performance and rate performance.
[0043] (2) The cathode material provided by the present invention can improve the compaction density of the cathode material by controlling the doping amount of K element, thereby increasing the energy density of the cathode sheet; on the other hand, by co-doping the cation M element and K element, the stability of oxygen in the cathode material can be improved, so that the cathode material has a higher specific capacity and energy density.
[0044] (3) The sodium-ion battery provided by the present invention has high specific capacity, high energy density, and stable interface under high voltage, and has excellent cycle stability and rate performance. Attached Figure Description
[0045] Figure 1 Electron micrograph of the cathode material in Example 1.
[0046] Figure 2 XRD pattern of the cathode material in Example 1. Detailed Implementation
[0047] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0048] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0049] Example 1
[0050] Cathode material preparation
[0051] (1) Cobalt sulfate and aluminum sulfate were mixed in a molar ratio of Co to Al of 0.965:0.035 and deionized water was added to obtain a mixed solution. A precipitant and a complexing agent were added to the mixed solution to obtain a reaction solution. The pH of the reaction solution was adjusted to 7.5, and a coprecipitation reaction was carried out under stirring to obtain a coprecipitate. The coprecipitate was sintered at 700℃ to obtain Al-doped (Co) 0.965 Al 0.035 )3O4 precursor;
[0052] (2) According to the stoichiometric ratio, (Co) 0.965 Al 0.035 A mixture of Na, Co, and K precursors was prepared by mixing Na, Co, and K in a molar ratio of 0.72:0.965:0.002 to obtain a powdered mixture. This powdered mixture was then sintered at 800°C for 24 hours in air to obtain a cathode material containing Co, Al, and K elements, with the chemical formula Na₂O₄. 0.72 Co 0.965 Al 0.035 K 0.002 ;
[0053] Positive electrode preparation
[0054] Weigh the prepared positive electrode material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF), and disperse them in an appropriate amount of N-methylpyrrolidone (NMP) at a weight ratio of 97:1.5:1.5. Stir thoroughly to form a uniform positive electrode slurry. Coat the positive electrode slurry onto the positive electrode current collector aluminum foil, and then dry, roll, and cut to obtain the positive electrode sheet.
[0055] Example 2
[0056] The other operations are the same as in Example 1, except that in step (2), the mixture of Na, Co, and K is prepared by mixing in a molar ratio of 0.72:0.965:0.003 to obtain a powdered mixture. The chemical formula of the prepared cathode material is Na. 0.72 Co 0.965 Al 0.035 K 0.003 .
[0057] Example 3
[0058] The other operations are the same as in Example 1, except that in step (2), the mixture of Na, Co, and K is prepared in a molar ratio of 0.72:0.965:0.001 to obtain a powdered mixture. The chemical formula of the prepared cathode material is Na. 0.72 Co 0.965 Al 0.035 K 0.001 .
[0059] Comparative Example 1
[0060] Other operations are the same as in Example 1, except that in step (2), Na, Co, and K are mixed in a molar ratio of 0.72:0.965:0 to obtain a mixture powder. The chemical formula of the prepared positive electrode material is Na. 0.72 Co 0.965 Al 0.0352 .
[0061] Comparative Example 2
[0062] The other operations are the same as in Example 1, except that in step (2), the mixture of Na, Co, and K is prepared by mixing in a molar ratio of 0.72:0.965:0.008 to obtain a powdered mixture. The chemical formula of the prepared cathode material is Na. 0.72 Co 0.965 Al 0.035 K 0.008 .
[0063] Test case
[0064] The above embodiments and comparative examples all used CR2032 coin cells to study the electrochemical performance of the cathode material. The preparation method of the coin cell is as follows:
[0065] In a glove box, the above-prepared positive electrode, sodium negative electrode, PP / PE / PP three-layer separator, and 1 mol / L NaPF6 / (EC+DEC) electrolyte (volume ratio 1:1) were assembled into a button cell for electrochemical testing.
[0066] The performance testing process for the button batteries prepared above is as follows:
[0067] The test temperature was 25℃, and the voltage range was 2.0–4.0V. The first five cycles were used for rate performance testing. During charging, the battery was charged at a constant current of 0.1C until the voltage reached 4.0V. During discharging, the battery was discharged at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C. Then, a 50-cycle performance test was conducted at a charge / discharge rate of 0.5C and a voltage range of 2.0–4.0V. The capacity retention rate (%) of the sodium-ion battery after 100 cycles = (Discharge capacity of the 105th cycle / Discharge capacity of the 6th cycle) × 100%.
[0068] Table 1. Rate performance and cycle performance test results of the button batteries in the examples and comparative examples.
[0069]
[0070] As can be seen from the specific test results of the examples and comparative examples in Table 1, the cathode materials of the examples have higher specific capacity, rate performance, and cycle performance. Compared with the examples, Comparative Examples 1 and 2 show that K doping has a certain improvement on the electrochemical performance of the cathode material, but the doping amount needs to be controlled within a certain range, as excessive doping will reduce the electrochemical performance.
[0071] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that, The cathode material is a sodium transition metal oxide containing Na, Co, K, and M elements, wherein the M element is selected from Al; the molar amount of K element per mole of cathode material is n. K The molar amount of Co in a unit mole of cathode material is n. Co The molar amount of element M in one mole of cathode material is n. M The n K and n Co+ n M The ratio is 0 <n K / n Co+ n M <0.005; The molar amount of Na per mole of cathode material, n Na It is 0.70 <n Na <0.76; The molar amount of K in a unit mole of cathode material, n K 0 <n K <0.005; The cathode material has a P2 phase stacking structure and belongs to the P63mc space group.
2. The cathode material according to claim 1, characterized in that, The molar amount n of element M in a unit mole of cathode material M 0 <n M <0.
05.
3. The cathode material according to claim 1, characterized in that, The chemical formula of the positive electrode material is: Na x K a Co 1- b M b O2, 0.7<x<0.76, 0<a<0.005, 0≤b<0.05, wherein M is as defined above.
4. The cathode material according to claim 1, characterized in that, The median particle size of the cathode material is 5 μm to 20 μm; the compaction density of the cathode material is 3.0 to 4.5 g / cm³. 3 .
5. The cathode material according to any one of claims 1-4, characterized in that, X-ray diffraction testing revealed that the cathode material possesses at least (002) peak, (102) peak, (103) peak, and (104) peak, with the (002) peak exhibiting the highest intensity. Furthermore, the peak intensities of the (102) peak, (103) peak, and (104) peak satisfy the condition I... (103) (104) (102) . 6. A positive electrode plate, characterized in that, The positive electrode sheet comprises the positive electrode material according to any one of claims 1-5.
7. A sodium-ion battery comprising the positive electrode material according to any one of claims 1-5, or comprising the positive electrode sheet according to claim 6.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material and preparation method thereof
CN113889603A
Combined metal oxide, positive-electrode active substance for sodium secondary cell, positive electrode for sodium secondary cell, and sodium secondary cell
WO2014115772A1
